2021
DOI: 10.3324/haematol.2021.278802
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of geriatric consultation versus standard care in older adults with hematologic malignancies

Abstract: We conducted a randomized controlled trial in older adults with hematologic malignancies to determine the impact of geriatrician consultation embedded in our oncology clinic alongside standard care. From February 2015 to May 2018, transplant-ineligible patients age ii75 years who presented for initial consultation for lymphoma, leukemia, or multiple myeloma at Dana-Farber Cancer Institute (Boston, MA) were eligible. Pre-frail and frail patients, classified based on phenotypic and deficitaccumulation approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 60 publications
0
38
0
Order By: Relevance
“…Three randomised controlled trials reported on the effect of the geriatric assessment on communication and care planning [12,20,24]. The results were consistent across trials for these outcomes.…”
Section: Effect On Communication and Care Planningmentioning
confidence: 84%
See 4 more Smart Citations
“…Three randomised controlled trials reported on the effect of the geriatric assessment on communication and care planning [12,20,24]. The results were consistent across trials for these outcomes.…”
Section: Effect On Communication and Care Planningmentioning
confidence: 84%
“…Overall, 29 studies addressed the comparison between the oncologic treatment plan before and after geriatric assessment, of which 21 described the change in treatment plan for individual patients [8,9,13,14,16,21,29,33,35,[39][40][41][42]48,52,53,59,60,66,72] and eight described differences in treatment choice between cohorts that did or did not undergo a geriatric assessment [10,20,23,26,46,55,57,63]. Three studies discussed the effect on communication and care planning [12,20,23]. Thirty-three studies reported on the number and type of recommended non-oncologic interventions [9,11,13,15,[17][18][19]22,25,[27][28][29]31,32,[36][37]…”
Section: Duplicatesmentioning
confidence: 99%
See 3 more Smart Citations